2017
DOI: 10.1136/archdischild-2015-310023
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in children: state of the art and future perspectives

Abstract: In this review, we provide a state of the art of liver transplantation in children, as the procedure is now carried out for more than 30 years and most of our paediatric colleagues are managing these patients jointly with liver transplant centres. Our goal for this article is to enhance the understanding of the liver transplant process that a child and his family goes through while explaining the surgical advances and the associated complications that could happen in the immediate or long-term follow-up. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 37 publications
0
40
0
2
Order By: Relevance
“…Since most complications related to the transplantation occur in the first year, children were included one year after transplantation, whereby we assumed that children settle in a stable pattern of PA after one year. Other inclusion criteria for this study were a normal graft function, defined as total bilirubin below 10 mmol/L, INR below 1.2, and albumin more than 38 g/L, and being able to follow test instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most complications related to the transplantation occur in the first year, children were included one year after transplantation, whereby we assumed that children settle in a stable pattern of PA after one year. Other inclusion criteria for this study were a normal graft function, defined as total bilirubin below 10 mmol/L, INR below 1.2, and albumin more than 38 g/L, and being able to follow test instructions.…”
Section: Methodsmentioning
confidence: 99%
“…New surgical techniques and immune-suppressive medication have improved treatment and survival of children after liver transplantation. 1 One-year survival of children undergoing liver transplantation is 93% and 5-year survival 88%. 2 In the Netherlands, 5-year survival has increased in the last 20 years from 71% to 83%.…”
Section: Introductionmentioning
confidence: 99%
“…For inborn errors of metabolism children (n = 9), the proportion with scores <70 on FSIQ, PIQ, VIQ, VMI, and GAC was 33 Others have found similar neurocognitive and HRQL outcomes in children after liver transplant. [4][5][6][7][8][9][10][11][12][15][16][17][18] In our study, the average FSIQ, PIQ, and VIQ were within one-half SD of population norms, suggesting no clinically discernible differences from the population as a group; however, there were much higher than expected proportions of patients below 1 and 2 SD of population means. The SPLIT longitudinal study found that FSIQ was 71-85 in 29% of those assessed and <70 in 7%.…”
Section: Times Expected Proportion (P-value)mentioning
confidence: 64%
“…4,15,17 HRQL outcomes often were lower than in healthy controls and comparable to those of children with other chronic diseases. 16,18 We previously reported neurocognitive outcomes at kindergarten entry in 33 children who had liver transplant at age under 3 years at our center. 17 That report was limited by the small number of patients that precluded multiple regression analyses for predictors of outcomes and lack of data for HRQL and functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation is a well‐established treatment and a standard of care for children with end‐stage liver disease and liver‐based metabolic diseases. Improved surgical techniques, modern immunosuppressive regimens and highly developed peri‐ and postoperative intensive care increased success rates for long‐term patient survival up to 90% . Despite excellent survival rates, complications after pLT still occur.…”
Section: Introductionmentioning
confidence: 99%